Acute Rhinosinusitis as an Infrequent Cause of Symptomatic Cluster Headache: Report of Seven Cases - Balgetir, Ferhat; Avci, Deniz; Gonen, Murat; Tasci, Irem (Mre Press, 2019)
Cluster headache (CH) is a primary headache disorder characterized by unilateral headache attacks lasting 15 to 180 minutes, occurring between two and eight times a day, and accompanied by autonomic symptoms ipsilateral to the pain. However, cases of symptomatic CH that occur secondary to an underlying structural pathology have also been reported in the literature. In this report, seven patients are presented who were admitted with signs of CH and diagnosed with acute rhinosinusitis depending on extensive clinical and radiologic examinations. Symptomatic CH, though rarely reported in the literature compared to CH, should be kept in mind in patients presenting with the first attack of CH. Moreover, in such patients, whether the pain becomes worse when bending forward and becomes sensitive on palpation should be questioned, and a radiologic work-up should be performed to rule out secondary causes such as rhinosinusitis. In the present cases, the resolution of CH attacks with acute sinusitis therapy confirmed the diagnosis.
Keywords: cluster headache; inflammation; pain; rhinosinusitis